Development Of Animated Learning Applications For Weathering Topics of Form 6 Geography - Othman, Nurul Farhana; Hamid, Hashima; Madar, Ahmad Rizal (Research and Innovation in Technical and Vocational Education and Training, 2022)
Animated learning applications can be one of the good teaching aids to deliver subject content like Geography subjects because this subject has been perceived as a difficult subject in the school curriculum that difficult to teach. In general, this android application was developed for assessing students to more understanding about weathering topic since it was involved the prolong process and needed physically attended at the places which troubled for teachers and students. The ADDIE model (analysis, design, development, implementation, evaluation) was chosen as the methodology for the development of this project which used Adobe Animate CC and Adobe Illustrator CS software. Developers use the Expert Checklist Form tool for assessments and expert verification form reviews. This application is reviewed by three (3) experts consisting of two (2) lecturers on FPTV and one (1) of Geography Teacher at Kolej Tingkatan Enam Sultan Sallehuddin, Kedah based on content design, design interface design and interaction design. The data obtained and analyzed are in the form of frequency. It was found that all the experts agreed that this application is good to present the content of weathering topic and can be used as a teaching tool (ABBM) for teachers teaching STPM Geography subjects. Hopefully this application will be enhance by others developers to make sure that it will present completely the whole process of the weathering and others physicaly geography process was happened.